Design and development of mild steel die for production of hip-bone joint - Shaha, Sugrib Kumar; Maleque, Md. Abdul; Dyuti, S.; Haque, Md. Mohafizul (2010)
Failure of hip bone joint is commonly caused by injuries, arthritis or aging factor. Currently, Ti-6Al-4V alloy has been dominating for medical applications; with uses extending across many orthopedic, dental and maxillofacial devices as well as the cardiovascular products. The production technique with this material is not economical and thus, less expensive material and less expensive production procedure have been searching. Cobalt based biocompatible material has been started to use and casting technique are being employed to reduce the cost. In order to produce a typical hip-bone joint by casting process, a die or mould is required. This study includes the modification of design together with fabrication of a typical hip joint casting dies with mild steel for squeeze casting. The hip-bone joint design has been generated using CATIA V5 software. Two slabs mild steel dies were machined on Vertical Machining Center (VMC) using appropriate tools.